The Cambridge encyclopedia of child development - Hopkins, Brian, 1940-; Barr, Ronald G.; Michel, George F., 1944-; Rochat, Philippe, 1950- (Gale virtual reference library., 2005)
An authoritative, accessible and up-to-date account of all aspects of child development. Written by an international team of leading experts everything from neonatal development to education, neuroscience, theories and research methods, physical development, social development, cognitive development, psychopathology and parenting are covered. Essential reading for everyone interested in children.